2019
DOI: 10.1016/j.artd.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of new interactive patient-provider software improves patient satisfaction and outcomes—a retrospective single-center study

Abstract: Background While a number of studies have explored patient- and provider-related factors contributing to quality of care, few studies have explored the role of technology in improving quality and optimizing patient-provider communication. This study explores the use of an interactive patient-provider software platform (IPSP) at a single institution. Specifically, we compared: (1) patient satisfaction scores, (2) complication rates, and (3) readmission rates before and after the use of an IPSP on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Furthermore, clinical findings acquired by mobile applications were consistent with those of in-person visits. 23,25,26,34 In addition, this study revealed an overall increased rate of postoperative survey completion with the use of a mobile application in comparison with in-office forms. [26][27][28]49 The use of a mobile application may be an opportunity for surgeons to effectively gather valuable data regarding patient feedback and functional outcomes and may help reduce unscheduled visits because of the added and improved communication such an intervention provides.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, clinical findings acquired by mobile applications were consistent with those of in-person visits. 23,25,26,34 In addition, this study revealed an overall increased rate of postoperative survey completion with the use of a mobile application in comparison with in-office forms. [26][27][28]49 The use of a mobile application may be an opportunity for surgeons to effectively gather valuable data regarding patient feedback and functional outcomes and may help reduce unscheduled visits because of the added and improved communication such an intervention provides.…”
Section: Discussionmentioning
confidence: 70%
“…Four articles reported on mobile applications ability to reduce postoperative unscheduled visits, and all four supported their use. 23,26,33,34 Two articles reported on the reduction of unscheduled office or emergency department visits when compared with control groups, and two reported on the accuracy between…”
Section: Prevention Of Unscheduled Visitsmentioning
confidence: 99%
“…Using the Oswestry Very Short Form, a measure of patient satisfaction, providers were able to assess whether patients were doing well without them attending clinic. PROMs and functional outcomes can also be collected with MA-based interactive patient-provider platforms 12 . A photograph-based smartphone MA was developed and implemented in a series of patients undergoing knee replacement to track their ROM remotely.…”
Section: Outcomes Acquisitionmentioning
confidence: 99%
“…Effective communication is a central component of highquality health care 1 that leads to better patient outcomes when successfully completed. [2][3][4] Unfortunately, productive health communication presents many challenges for health care providers and patients and can contribute to health inequity. 5,6 For instance, providers must acquire, synthesize, and present massive amounts of complex information to patients 7 ; and patients must receive, process, and use that information, which, despite best intentions, is frequently presented in a complicated format or riddled with advanced medical terminology.…”
Section: Background and Significancementioning
confidence: 99%